PENENTUAN PEMAKAIAN DOSIS DAN MACAM BIOFERTILIZER DALAM PEMBUATAN PUPUK ORGANIK PADAT TERHADAP KANDUNGAN UNSUR MAKRO NUTRIEN DAN ANALISIS FINANSIAL - Sulistyaningsih, Catur Rini; Harsono, Sri (Berkala Ilmiah AGRIDEVINA, 2017)
The purpose of this study is to (1) find out the influence of organic fertilizers in the formof bio-fertilizer deployment puktan with a dose of 0.4 liters/100 kg of livestock excrement,and starter MOLE with a dose of 0.4 liters/100 kg of excrement of livestock inaccordance with the standardization of Fertilizer compost N0:28/Permentan/SR.130/5/2009,22 May 2009, and 2005 to plant vegetables (spinach, mustard greens andkale), (2) know the size of the dose and manner of bio-fertilizer is most effective in themanufacture of solid organic fertilizers towards growth and crop production (spinach,mustard greens and sprouts land) (3) to know financial analysis results for organicfertilizer which fermented by starter bio-fertilizer MOL and bio-fertilizer Puktan. Thebest results from the various levels of the dose and type of bio-fertilizers will be producedfor the next use to increase the production of vegetable crops in the form of spinach, kaleand mustard greens. All the data obtained were analyzed using analysis of varian, i.e. thefactorial design. When there are different results continued with a real difference testbetween the mean i.e. Duncan (DMRT) Test with SPSS model analysis. From the resultsof the analysis, the use of dose and range of bio-fertilizer in the manufacture of solidorganic fertilizers provide a significant impact towards growth and crop production, themost effective against land Cress plant growth than spinach and mustard greens.Whereas against production, are most effective in plant mustard greens. The results of theeconomic analysis fertilizer prices are fermented with bio-fertilizer starter MOLapparently gained provit larger compared with the fermented fertilizer with bio-fertilizerPuktan (USD 503/kg > Rp 470/kg).